Education Quality Problems in the Independent Curriculum Era - Sugiarti, Erna; Baehaqi, Luqman; Jumrodah (Jurnal Manajemen Pendidikan, 2025)
Background The problem of education quality in Indonesia is a complex challenge that requires a multifaceted approach. By improving access and quality of education, increasing teacher professionalism, and developing a relevant curriculum, it is hoped that the quality of education in Indonesia can improve significantly. Purpose The purpose of writing this article is to analyze various problems that affect the quality of education in Indonesia in the era of the independent curriculum and identify potential solutions to overcome these problems. Design/method/approach The method used in this article is literature study. Results The results of this research explain that from various problems with the quality of education in the era of the independent curriculum, the government continues to strive to improve and improve the quality of education, unequal access and quality of education, improving teacher quality and professionalism, improving educational infrastructure and facilities so as to achieve the goal of national education to create the next generation. superior and integrated successor. Contribution/value To overcome this problem, the government needs to increase teacher training programs, especially in hard-to-reach areas, apart from that, there needs to be a larger budget allocation for improving educational facilities, and educational equality policies must be a priority.